The efficacy and safety of half-dose glucocorticoids combined with rituximab versus high-dose glucocorticoids for initial treatment of minimal change disease: a single-center experience - Li, Xueting; Yan, Peng; Zhang, Lu; Qiao, Wei; Xue, Zhengbiao; Fang, Xiangdong; Ke, Ben; Zhu, Shuying (Frontiers in Pharmacology, 2025)
BackgroundMinimal change disease (MCD) is a podocytopathy more commonly seen in children, but it also accounts for 10%–25% of adult nephrotic syndrome. High-dose oral glucocorticoids were recommended for initial treatment of MCD. However, long-term use of systemic corticosteroids is associated with significant adverse events, such as steroid-induced diabetes and infections. The aim of this study was to investigate the clinical efficacy and safety of half-dose glucocorticoids combined with rituximab (RTX) for the initial treatment of MCD.MethodsWe recruited 74 patients with MCD confirmed by renal biopsy. Twenty patients were treated with RTX alone with 1000 mg at d1 and d15, 28 patients received half-dose prednisolone (0.5 mg/kg) per day combined with RTX with 1000 mg at d1, and 26 patients received high-dose prednisolone (1 mg/kg) per day. Treatment responses, including complete remission (CR) and partial remission (PR), and outcome adverse events such as steroid-induced diabetes and infections were compared among the three groups after 12 months of follow-up.ResultsAt the 12-month follow-up, the CR rates were 50%, 96.4%, and 96.2% for the RTX group, half-dose prednisolone combined with RTX group, and high-dose prednisolone group, respectively. There was no statistical difference between the half-dose prednisolone combined with RTX group and high-dose prednisolone group on CR and PR and kidney function (P > 0.05). Compared with the high-dose prednisolone group, the half-dose prednisolone combined with RTX group had a reduced incidence of adverse events of steroid diabetes (P = 0.041), especially in patients older than 55 years of age.ConclusionThe efficiency of half-dose prednisolone combined with RTX is not inferior to the recommended treatment regimen, and this regimen can effectively reduce the incidence of steroid-induced diabetes in patients with MCD. Moreover, we recommend a half-dose prednisolone combined with RTX treatment for elderly patients with MCD.